Association of overweight, obesity, and recent weight loss with colorectal cancer risk - Mandić, Marko; Safizadeh, Fatemeh; Niedermaier, Tobias; Hoffmeister, Michael; Brenner, Hermann (JAMA network open, 2023)
Overweight and obesity, conditions with rising prevalence in many countries, are associated with increased colorectal cancer (CRC) risk. However, many patients with CRC lose weight before diagnosis, which may lead the association to be underestimated.To evaluate the association of body mass index (BMI) and weight change with CRC risk when considering BMI at different time frames, with the intention to account for prediagnostic weight loss.This population-based case-control study was conducted in southwestern Germany between 2003 and 2021. Cases with a first diagnosis of CRC and controls (frequency matched by age, sex, and county) with comprehensive risk factor information and self-reported weight at different time points were included. Data were analyzed between October 2022 and March 2023.BMI and weight change at different time frames before the time of diagnosis (cases) or recruitment (controls).Association of BMI and weight change at various points in time before and up to diagnosis with CRC, assessed by multivariable logistic regression with comprehensive confounder adjustment.A total of 11887 participants (6434 CRC cases, 5453 controls; median [IQR] age, 69 [61-77] years; 7173 male [60.3%]) were included. At the time of diagnosis, 3998 cases (62.1%) and 3601 controls (66.0%) were overweight or obese, suggesting an inverse association between excess weight and CRC risk. Conversely, we found significant positive associations of overweight (adjusted odds ratio [aOR], 1.27; 95% CI, 1.03-1.56), obesity (aOR, 2.09; 95% CI, 1.61-2.70), and a 5-unit increase in BMI (aOR, 1.35; 95% CI, 1.21-1.50) with CRC risk when using BMI measured 8 to 10 years before diagnosis. High BMI as a risk factor for CRC was increased as earlier periods before diagnosis were examined, with the association being particularly pronounced using BMI at least 8 years before diagnosis. An opposite trend was found for the association of weight loss (at or exceeding 2 kg) with CRC, with the greatest effect sizes occurring for weight loss within 2 years before diagnosis (aOR, 7.52; 95% CI, 5.61-10.09), and gradually decreased for earlier intervals.In this population-based case-control study, accounting for substantial prediagnostic weight loss further highlighted the association of overweight and obesity with CRC risk.
Online veröffentlicht: 21. April 2023
Gesehen am 28.11.2023